Prostate Cancer Screening in Greece: Current Facts - Stamatiou, Konstantinos; Lardas, Michael; Kostakos, Evagelos; Koutsonasios, Vasilios; Lepidas, Dimitrios (Urology Journal, 2009)
Introduction: The purpose of the current article is to summarize the existing literature focusing on the current status of prostate cancer screening behaviour in Greece. Materials and Methods: We identified studies published from 2000 onwards by searching the MEDLINE database of the National Library of Medicine. Initial search terms were prostate-specific antigen screening, prostate cancer screening, and Greece. Bibliographic information of the selected publications was checked for relevant publications not included in the MEDLINE search. Results: Currently in Greece, there is no official recommendation for prostate cancer screening, and thus, its practice depends on the social and educational status of the patient and where the patient lives in Greece. Conclusion: We conclude that patients should be thoroughly informed of the limitations of prostate cancer screening by prostate-specific antigen test, and in consultation with urological specialists, make their personal decision of whether to receive it. Therefore, a project to support shared decision-making and informed choice for men considering testing for prostate cancer should be undertaken.